2015
DOI: 10.1111/jocn.12856
|View full text |Cite
|
Sign up to set email alerts
|

The role as moderator and mediator in parent education groups – a leadership and teaching approach model from a parent perspective

Abstract: The role as moderator and mediator in parent education groups -a leadership and teaching approach model from a parent perspective, 2015, Journal of Clinical Nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
(62 reference statements)
0
16
0
10
Order By: Relevance
“…The findings might be explained by earlier studies revealing a lack of training in group leadership for leaders (Forslund Frykedal et al, ; Lefèvre et al, ), lack of competence in managing groups and teaching methods, as well as difficulties in identifying parents' needs (Forslund Frykedal et al, ). The results also support and can provide better understanding of parents' reports of a shortage of group activities (Berlin et al, ; Forslund Frykedal & Rosander, ), a lack of leadership ability in PE groups (Berlin et al, ; Forslund Frykedal et al, ), and the most frequent teaching method used in PE groups being lectures (Berlin et al, ). The present study showed that leaders used their expert role most of the time, and mediated information and expert knowledge.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The findings might be explained by earlier studies revealing a lack of training in group leadership for leaders (Forslund Frykedal et al, ; Lefèvre et al, ), lack of competence in managing groups and teaching methods, as well as difficulties in identifying parents' needs (Forslund Frykedal et al, ). The results also support and can provide better understanding of parents' reports of a shortage of group activities (Berlin et al, ; Forslund Frykedal & Rosander, ), a lack of leadership ability in PE groups (Berlin et al, ; Forslund Frykedal et al, ), and the most frequent teaching method used in PE groups being lectures (Berlin et al, ). The present study showed that leaders used their expert role most of the time, and mediated information and expert knowledge.…”
Section: Discussionmentioning
confidence: 54%
“…Parents prefer leaders who can create participative and interactive learning environments instead of a more lecture‐type style (Berlin et al, ). Obviously, it is a challenge to give up the expert role and provide opportunities to parents to set the agenda (Baldwin & Phillips, ; Forslund Frykedal & Rosander, ). Therefore, giving leaders opportunities to develop these abilities is important for learning in a PE group environment to provide better parental support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CHS programme is well appreciated by the parents and 98–99% participate, although only 49% participate in the parental groups (Centre of Excellence for Child Health Service ). There is little research on group leadership in parental groups for parents or parents to be (Thielen , Forslund Frykedal & Rosander ), but a trusting and permissive climate in these groups as well as how the groups are managed is seen to be of importance to parental satisfaction (Petersson et al . , Nolan et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, most CHC nurses lack formal group leadership education or training. Parental groups are offered as a complement to individual parental support and are meant to provide possibilities for parents in the same situation to share experiences and serve as resources for each other (Forslund Frykedal & Rosander ). Lack of structure and active leadership in parental groups could cause this opportunity to be missed (Hjalmhult et al .…”
Section: Introductionmentioning
confidence: 99%